Pemanfaatan Media Microsoft Power Point dalam Pembelajaran Kemahiran Berbahasa Arab pada Era Digital - Mabruri Mabruri; Hamzah Hamzah (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2020)
Life in the Digital Age is automatically required by someone not to be out of date with a device or device such as a computer or laptop. Data and information even the basic needs of a student can be said to have been stored in a system called a digital system. Everything is available in one system that can and is freely accessed by anyone. as a teacher in utilizing sophisticated tools in this digital age, it is demanded to adjust and apply in the form of a learning as the medium. So one of the things that can be used by a teacher is to use Microsoft Power Point program as a medium in innovating a learning. This paper aims to develop an Arabic learning media by using Microsoft Power Point program as a medium in learning Arabic proficiency.